(Un‐)expected nocturnal activity in "Diurnal" Lemur catta supports cathemerality as one of the key adaptations of the lemurid radiation. Issue 1 (26th November 2012) - Donati, Giuseppe; Santini, Luca; Razafindramanana, Josia; Boitani, Luigi; Borgognini‐Tarli, Silvana
Abstract The ability to operate during the day and at night (i.e., cathemerality) is common among mammals but has rarely been identified in primates. Adaptive hypotheses assume that cathemerality represents a stable adaptation in primates, while nonadaptive hypotheses propose that it is the result of an evolutionary disequilibrium arising from human impacts on natural habitats. Madagascar offers a unique opportunity to study the evolution of activity patterns as there we find a monophyletic primate radiation that shows nocturnal, diurnal, and cathemeral patterns. However, when and why cathemeral activity evolved in lemurs is the subject of intense debate. Thus far, this activity pattern has been regularly observed in only three lemurid genera but the actual number of lemur species exhibiting this activity is as yet unknown. Here we show that the ring‐tailed lemur, Lemur catta, a species previously considered to be diurnal, can in fact be cathemeral in the wild. In neighboring but distinct forest areas these lemurs exhibited either mainly diurnal or cathemeral activity. We found that, as in other cathemeral lemurs, activity was entrained by photoperiod and masked by nocturnal luminosity. Our results confirm the relationship between transitional eye anatomy and physiology and 24‐h activity, thus supporting the adaptive scenario. Also, on the basis of the most recent strepsirrhine phylogenetic reconstruction, using parsimony criterion, our findings suggest pushing back the emergence of cathemerality to stem lemurids. Flexible activity over 24‐h could thus have been one of the key adaptations of the early lemurid radiation possibly driven by Madagascar's island ecology. Am J Phys Anthropol, 2012. © 2012 Wiley Periodicals, Inc.